2012
DOI: 10.1093/alcalc/ags125
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Patterns and Their Predictive Factors in CONTROL: a 12-Month Prospective Study in a Sample of Alcohol-Dependent Patients Initiating Treatment

Abstract: In this sample, the drinking patterns of alcohol-dependent patients were predicted by baseline factors, i.e. depression, living alone or alcohol-related consequences and findings that may inform clinicians about the likely drinking patterns of their alcohol-dependent patient over the year following the initial evaluation for alcohol treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 40 publications
0
10
0
2
Order By: Relevance
“…CONTROL included 143 participants, followed for up to 487 days. Full details of the CONTROL study design have been published previously [ 26 , 27 ]. The primary objective of CONTROL was to describe the drinking patterns of patients with alcohol dependence and their baseline predictive factors during a 12-month period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CONTROL included 143 participants, followed for up to 487 days. Full details of the CONTROL study design have been published previously [ 26 , 27 ]. The primary objective of CONTROL was to describe the drinking patterns of patients with alcohol dependence and their baseline predictive factors during a 12-month period.…”
Section: Methodsmentioning
confidence: 99%
“…The primary objective of CONTROL was to describe the drinking patterns of patients with alcohol dependence and their baseline predictive factors during a 12-month period. More specifically, it intended to describe the population of patients with alcohol dependence, their disease management and their evolution in terms of alcohol consumption, social consequences, quality of life and resource use, after an initial evaluation for alcohol treatment [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Kravitz ve ark., (18) yaptıkları çalışmada ise, alkole başlama yaşının, bağımlılık süresinin, içme yoğunlu-ğunun, geçmiş yoksunluk deneyimlerinin, Daeppen ve ark., (19) önceki detoksifikasyon tedavileri sayısının ve alkol-maddeye yine başlama nedenlerinin yaşam kalitesini etkileyebileceğini ileri sürmüşlerdir. (20) , Goldstein ve ark., (21) alkol bağımlılarında yaşam kalitesinin temel belirliyicilerinin, önem sırasına göre, bağımlılık şiddeti, iş durumu, psikiyatrik öykü, kullanılan alkolün sıklığı ve miktarı, adsız alkolikler (AA) başvurusu, genel sağ-lık durumu, yaş, cinsiyet ve eğitim durumu olduğunu belirtmişlerdir.…”
Section: Alkol Bağımlılığında Yaşam Kalitesiunclassified
“…Depresif ve depresif olmayan alkol bağım-lısı kadın hastaların incelendiği çalışmalarda, depresif kadın bağımlıların aile ilişkileri temel olmak üzere tüm alanlarda depresif olmayanlara göre daha çok desteğe gereksinim duydukları ve daha sık hastane başvurularının olduğu gözlenmiştir (17,19) .…”
Section: Hunt Ve Mcewenunclassified
“…A review of the literature in which regression mixtures are used showed a lack of consensus in the specification of residual variances; some authors freely estimated the class-specific residual variance (Daeppen et al, 2013; Ding, 2006; Lee, 2013), while others constrained them to be equal across classes (Muthén & Asparouhov, 2009). Interestingly, the majority of the studies employing regression mixtures gave no information about residual variance specifications whether the equality constraint has been imposed or not (Lanza et al, 2013; Lanza, Kugler, & Mathur, 2011; Liu & Lu, 2011; Schmeige, Levin, & Bryan, 2009; Wong & Maffini, 2011; Wong et al, 2012).…”
Section: Introductionmentioning
confidence: 99%